Effect Of Vitamin D Administration On Interleukin 6 (IL-6) Levels In Peritoneal Fluid In Endometrioma Patients - Singgeh Setyasworo; Arufiadi Anityo Mochtar; Erwinanto Erwinanto; Herman Kristanto; Hary Tjahjanto; Yuli Trisetiyono (RSUP Dr. Kariadi, 2024)
BACKGROUND: An endometrioma is a cyst that occurs when endometrial tissue grows on the epithelium of the ovary. Vitamin D is a steroid hormone that can be extracted from commonly available foods and can be synthesized by humans when exposed to sunlight. Vitamin D deficiency has been reported to be associated with various pathologies, including endometrioma. Vitamin D has been reported to have anti-angiogenic effects that may inhibit the growth of endometriotic implants. AIM: Proving the effect of vitamin D administration on interleukin 6 (IL-6) levels in peritoneal fluid in patients with endometrioma. METHOD: Experimental research with two group, post-test only design with single blind that carried out at Central General Hospital (RSUP) Dr. Kariadi Semarang. The research subject was 50 patients with endometrioma on ovary. The definite diagnosis of endometrioma is made based on histopathological examination of tissue samples after the patient undergoes surgery. Patients will be divided into 2 groups, namely the vitamin D3 supplementation group and placebo. The intervention was carried out by providing vitamin D3 50,000 IU/week for a month. Evaluation of serum vitamin D levels were obtained using venous blood samples immediately when the patient was undergoing surgery. Interlukin-6 levels were obtained using peritoneal fluid samples obtained when the patient underwent surgery. Statistical analysis was carried out using the Independent T Test, Mann-Whitney U, Dependent T Test and Wilcoxon. Results are significant if p <0.05. Statistical analysis was carried out using SPSS edition 26. RESULT: Peritoneal fluid interleukin-6 (IL-6) levels between the vitamin D supplementation group and the placebo group did not show a significant difference (p=0.554). CONCLUSION: Vitamin D supplementation in endometrioma patients is not associated with peritoneal fluid interleukin-6 (IL-6) levels.